Pemanfaatan Media Visual untuk Mengembangkan Keterampilan Menulis Teks Lanjutan pada Siswa SMPN 3 Pangkajene Sidrap - Anita Candra Dewi (Journal of Humanities, Social Sciences, and Education, 2025)
This study aims to examine the effect of using visual media in the form of series of images on the writing skills of advanced texts in junior high school students. This experimental study involved two groups, namely the experimental group that used visual media and the control group that did not use visual media. The data collected consisted of pretest and posttest scores taken from both groups to measure the improvement in writing skills after being given treatment. The results showed that the experimental group experienced a more significant increase in scores compared to the control group. The average increase in scores in the experimental group was 24.5 points, while in the control group it was only 7.5 points. The normality test conducted using the Kolmogorov-Smirnov test showed that the data of both groups were normally distributed, while the homogeneity test using the Levene test showed that the variances of both groups were homogeneous. Hypothesis testing conducted using the t-test showed that there was a significant difference between the experimental group and the control group in the posttest, with a significance value of 0.000 (<0.05). Based on these results, it can be concluded that visual media in the form of series of images is effective in improving the writing skills of advanced texts in junior high school students. This research contributes to the development of Indonesian language learning strategies, especially in optimizing the use of visual media as a more interesting and effective learning tool.